Pelatihan Manajemen Berbasis Teknologi Digital pada BUMG Ujong Baroh Kabupaten Aceh Barat - Alisman Alisman; Zainal Putra; Puput Arisna; M. Rahmat Hidayat; Rusdi Rusdi; Hartini Hartini; Yenni Ertika; Dedi Sufriadi (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
The purpose of this community service activity is to create a strong BUMDes in Gampoeng Ujong Baroh, Johan Pahlawan District, West Aceh Regency, both in terms of Innovation, institutions and financial management based on transparency and accountability. This community service was carried out in Gampoeng Ujong Baroh, Johan Pahlawan District, West Aceh Regency in June 2025. Management training was carried out in two sessions. The first training session was carried out by the community service with the material "Establishment of BUMDes and BUMDes Management". And the second session was related to the management of technology management in BUMDes. Participants who took part in the socialization/workshop activities were village heads, sub-district assistants and BUMDes administrators of Gampoeng Ujong Baroh, Johan Pahlawan District. The number of participants who took part in this activity was 20 people. The results of the community service formed an understanding of the behavior of Bumdes (BUMG) managers in the village in carrying out their business activities. Village-Owned Enterprise (Bumdes) managers understand how to explore village potential and develop it to become independent villages. They understand how to initiate, start, and determine diverse business types based on the potential of existing human resources. They are able to develop Village-Owned Enterprises (BUMG) as institutions capable of meeting the needs of the village community.